Off-Patent Transgenic Events: Challenges and Opportunities for New Actors and Markets in Agriculture - Rüdelsheim, Patrick; Dumont, Philippe; Freyssinet, Georges; Pertry, Ine; Heijde, Marc (Frontiers in Bioengineering and Biotechnology, 2018)
More than 20 years ago, the first genetically modified (GM) plants entered the seed market. The patents covering the first GM plants start to expire and they can be considered now as Off-Patent Events. Here we describe the challenges that will be faced by a Secondary Party by further use and development of these Off-Patent Events. Indeed, the conditions for Off-Patent Events are not available yet to form the basis for a new viable industry similar to the generic manufacturers of agrochemicals or pharmaceutical products, primarily because of (i) no harmonized global regulatory requirements for GM organisms, (ii) inaccessibility to regulatory submissions and data, and (iii) potential difficulties to obtain seeds and genetic material of the unique genotypes used to generate regulatory data. We propose certain adaptations by comparing what has been done in the agrochemicals and pharmaceuticals markets to facilitate the development of generics. Finally, we present opportunities that still exist for further development of Off-Patent Events in collaboration with Proprietary Regulatory Property Holders in emerging markets, provided (i) various countries approve these events without additional regulatory burdens (i.e., acceptance of the concept of data transportability), and (ii) local breeders agree to meet product stewardship requirements.